A consensus report on appropriate treatment optimization and transitioning in the management of moderate‐to‐severe plaque psoriasis. (26th February 2013) - Mrowietz, U.; de Jong, E.M.G.J.; Kragballe, K.; Langley, R.; Nast, A.; Puig, L.; Reich, K.; Schmitt, J.; Warren, R.B.
Abstract Background There is limited information on systemic and biological treatment optimization and transitioning in routine clinical practice. Objective To provide practical guidance on treatment optimization and transitioning for moderate‐to‐severe plaque psoriasis. Methods Dermatologists from 33 countries contributed to the Transitioning Therapies programme. Fourteen questions were identified. Answers were drafted based on systematic literature reviews (7/14 questions) and expert opinion (7/14 questions). Using a modified Delphi procedure, dermatologists from 30 countries voted on their level of agreement with each draft answer (scale: 1–9, strong disagreement to strong agreement). Consensus was defined as ≥75% of participants scoring within the 7–9 range. Results Consensus was achieved on the answers to all questions. Recommendations for the use of cyclosporine and methotrexate were agreed. Transitioning from a conventional systemic therapy to a biological agent may be done directly or with an overlap (if transitioning is required because of lack of efficacy) or potentially with a treatment‐free interval (if transitioning is required for safety reasons). Combination therapy may be beneficial. Continuous therapy for patients on biologicals is strongly recommended. However, during successful maintenance with biological monotherapy, a dosage reduction may be considered to limit drug exposure, although this may carry the risk of decreased efficacy. Switching biologicals for reasons of efficacy should be done without a washout period, but switching for reasons of safety may require a treatment‐free interval. Conclusion This consensus provides practical guidance on treatment optimization and transitioning for moderate‐to‐severe plaque psoriasis, based on literature reviews and the expert opinion of dermatologists from across the globe.